2021
DOI: 10.1177/0954008321989410
|View full text |Cite
|
Sign up to set email alerts
|

High toughness and excellent electrical performance bismaleimide resin modified by hyperbranched unsaturated polyester of flexible aliphatic side chains

Abstract: Because of its flawed toughness, the scope of application of bismaleimide resin (BMI) in the field of aeronautics, industry and electricity is greatly restricted. Herein, a novel Hyperbranched unsaturated polymers (HBP) with the flexible chains grafted was incorporated to reinforce BMI resin’s toughness, where the new interpenetrating networks (IPN) structure was formed. The rich unsaturated double bond of HBP polyester could react with the BMI resin for chemical crosslinking and be used for the toughening age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Figure 9 b shows the volume resistivity of BMI-NH 2 ; it can be intuitively seen that the volume resistivity of samples was basically unchanged. This was because the resin of the building branched structure multiplied the free volume of the system [ 31 ]. At the same time, the steric hindrance effect of the group resulted in a relatively compact structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 9 b shows the volume resistivity of BMI-NH 2 ; it can be intuitively seen that the volume resistivity of samples was basically unchanged. This was because the resin of the building branched structure multiplied the free volume of the system [ 31 ]. At the same time, the steric hindrance effect of the group resulted in a relatively compact structure.…”
Section: Resultsmentioning
confidence: 99%
“…The modified resin shows enhanced energy absorption capacity, thereby improving its mechanical performance. Another modification method is synthesizing BMI resin with a branched structure by designing the molecular structure, which can improve the mechanical strength of thermosetting polymer [ 29 , 30 , 31 , 32 ]. Jiang et al [ 33 ] designed a novel liquid multi-maleimide branched polysiloxane (PMI-HSi).…”
Section: Introductionmentioning
confidence: 99%
“…Composite materials, characterized by their multiphase composition involving two or more components, possess distinctive material properties and find wide-ranging applications in contemporary technological advancements. They notably exhibit significant advantages in mechanical properties and high-temperature resistance, critical attributes for a plethora of high-performance applications [1,2]. Among these, silicon carbide (SiC)/resin composites stand out for their exceptional properties.…”
Section: Introductionmentioning
confidence: 99%
“…Since modulus and breakdown strength are influenced by the content of cluster free volume, enhanced modulus and dielectric properties could be obtained with a certain content of free volume. Shi et al [ 33 ] used a newly synthesized hyperbranched unsaturated polyester molecule with flexible chains to improve the level of BMI properties. The results showed that the impact strength and flexural strength was increased by 211.1% and 209.3%, respectively, with an HBP mass of 20 wt.%.…”
Section: Introductionmentioning
confidence: 99%